2016
DOI: 10.1016/j.jviromet.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of a cytometric p24-capture bead-assay for the detection of main HIV-1 subtypes.

Abstract: The prevailing method to assess HIV-1 replication and infectivity is to measure the production of p24 Gag protein by enzyme-linked immunosorbent assay (ELISA). Since fluorescent bead-based technologies offer a broader dynamic range and higher sensitivity, this study describes a p24 capture Luminex assay capable of detecting HIV-1 subtypes A, B, C, D, circulating recombinant forms (CRF) CRF01_AE and CRF02_AG, which together are responsible for over 90% of HIV-1 infections worldwide. The success of the assay lie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Many studies highlighting the use of antibody from commercial hybridoma cell (clone 183-H12-5C) in detecting the HIV-1 capsid protein p24, 32 , 33 however until now it has yet to be used for therapeutic purpose of HIV-1/AIDS. With the fact that monoclonal antibodies (mAbs) are highly specific and stable, it becomes an attractive candidate for in vivo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies highlighting the use of antibody from commercial hybridoma cell (clone 183-H12-5C) in detecting the HIV-1 capsid protein p24, 32 , 33 however until now it has yet to be used for therapeutic purpose of HIV-1/AIDS. With the fact that monoclonal antibodies (mAbs) are highly specific and stable, it becomes an attractive candidate for in vivo treatment.…”
Section: Discussionmentioning
confidence: 99%
“…36 Tests have also been developed for the detection of the p24 protein in various subtypes of HIV-1. 37,38 The results have shown that the method is 91% more sensitive than the standard ELISA test and also has a lower cost. 37…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
“…37,38 The results have shown that the method is 91% more sensitive than the standard ELISA test and also has a lower cost. 37…”
Section: Diagnostic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations